State intervention in the market for corporate control - Szewczyk, Samuel H.; Tsetsekos, George P. (Journal of Financial Economics, 1992)
This study investigates the impact of Pennsylvania Senate Bill 1310 on the share prices of Pennsylvania corporations. Considered the most severe of the second-generation antitakeover laws, the statute limits the ability of shareholders to challenge management through the proxy process and eliminates the traditional fiduciary obligation of directors to promote shareholders' interests. We find that PA SB1310 significantly decreased share values, and estimate the loss to shareholders of Pennsylvania firms at $4 billion. However, firms with antitakeover charter amendments already in place were less affected, and firms that exempted themselves from PA SB1310 recovered a portion of shareholders' wealth.